Deficits in systemic biomarkers of neuroinflammation and growth factors promoting nerve regeneration in patients with type 2 diabetes and polyneuropathy. Issue 1 (27th November 2019) - Ziegler, Dan; Strom, Alexander; Bönhof, Gidon J; Kannenberg, Julia M; Heier, Margit; Rathmann, Wolfgang; Peters, Annette; Meisinger, Christina; Roden, Michael; Thorand, Barbara; Herder, Christian
Abstract : Introduction: The determinants and mechanisms contributing to diabetic sensorimotor polyneuropathy (DSPN) remain unclear. Since neuroinflammation and altered nerve regeneration have been implicated in the pathogenesis of both DSPN and neuropathic pain, we hypothesized that the corresponding biomarkers could be associated with DSPN in general and could have the potential to discriminate between the painful and painless DSPN entities. Methods: In a cross-sectional study using multimarker proximity extension assay technology we assessed 71 serum biomarkers including cytokines, chemokines, growth factors, receptors, and others in patients with type 2 diabetes with DSPN (DSPN+) (n=304) or without DSPN (DSPN−) (n=158) and persons with normal glucose tolerance (NGT) without polyneuropathy (n=354). Results: After adjustment for multiple testing and sex, age, body mass index, HbA1c, and smoking, the serum levels of 17 biomarkers (four cytokines, five chemokines, four growth factors, two receptors, two miscellaneous) were lower in DSPN+ than in DSPN− and NGT. In DSPN+, six of these biomarkers were associated with peripheral nerve function. The concentrations of 15 other biomarkers differed between NGT and both DSPN+ and DSPN−, but not between DSPN+ and DSPN−. No differences in biomarker levels were found between patients with painful (n=164) and painless DSPN (n=140). Conclusions: Deficits in systemic cytokines, chemokines, and growth factors promoting nerve regeneration in patients with type 2 diabetes are linked to polyneuropathy in general but not specifically to the painful or painless entity. Trial registration number: NCT02243475 .